Aesthetics of Hadroh Music in Islamic Education: A Study of Religious Thought and Spiritual Formation in Majlis Sholawat Bintang Songo - Fiko Savero; Muhammad Miftahuddin Adha; Shofiyullah Muzammil (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Hadroh music is a part of Islamic religious art traditions that have developed rapidly in Indonesia, especially through majlis sholawat. Hadroh is not only a form of entertainment but also a medium of religious preaching and spiritual strengthening for its participants. The aesthetics of hadroh music is an essential aspect for understanding how beauty, musicality, and spirituality merge within an artistic practice. However, studies on the aesthetics of hadroh music remain limited, particularly in the context of majlis such as Bintang Songo. This majlis is widely known for its hundreds of followers and its distinctive musical character. This study is important because it demonstrates how art can become both a cultural force and a spiritual bond for the community. This research employs a qualitative approach, chosen because the study focuses on collecting, observing, examining, and analyzing literature relevant to the theme of hadroh music aesthetics, especially within the practices of the Bintang Songo Majlis. The results show that the aesthetics of hadroh music in Bintang Songo lie in the combination of harmonious rebana arrangements, emotionally rich sholawat chants, and the spiritual interaction between vocalists, musicians, and the congregation. The uniqueness of Bintang Songo is its ability to create a festive religious atmosphere without losing the depth of spiritual meaning. These findings enrich the discourse on religious music in Indonesia by showing that the aesthetics of hadroh can serve as an effective medium of dakwah while also strengthening the cultural identity of Islam Nusantara. Moreover, this study opens new perspectives on the relationship between art, spirituality, and the social life of its participants. This research remains limited to a single majlis, namely Bintang Songo, so the generalization of its findings should be approached with caution. Further research is recommended to compare the aesthetics of hadroh music across other majlis sholawat to obtain a broader depiction of the diversity of hadroh aesthetics in Indonesia.